Effect of Depth of Total Intravenous General Anesthesia on Intraoperative Electrically Evoked Compound Action Potentials in Cochlear Implantation Surgery - Alhowary, Ala”a (Anesthesiol Res Pract, 2019)
PURPOSE: This study aims to compare the effect of the depth of total intravenous anesthesia (TIVA) on intraoperative electrically evoked compound action potential (e-ECAP) thresholds in cochlear implant operations. METHODS: Prospectively, a total of 39 patients aged between 1 and 48 years who were scheduled to undergo cochlear implantation surgeries were enrolled in this study. Every patient received both light and deep TIVA during the cochlear implant surgery. The e-ECAP thresholds were obtained during the light and deep TIVA. RESULTS: After comparing the e-ECAP means for each electrode (lead) between the light and deep anesthesia, no significant differences were detected between the light and deep anesthesia. CONCLUSION: The depth of TIVA may have no significant influence on the e-ECAP thresholds as there was no statistical difference between the light and deep anesthesia.